Role of LED versus Conventional Phototherapy in Full-Term Newborn having Jaundice Neonatorum - Sami Ullah; Fatima, Zeeshina; Sami, Hafiz Ahmad (Indus Journal of Bioscience Research, 2025)
Background: Neonatal jaundice, which is defined by elevated unconjugated bilirubin, affects the majority of newborns and, if severe, can result in acute bilirubin encephalopathy and kernicterus. Phototherapy is the first-line treatment for converting bilirubin into excretable isomers. Conventional systems using fluorescent or halogen bulbs provide broad-spectrum light, but generate excess heat, require frequent bulb changes, and produce uneven irradiance. The objective was to compare the effectiveness, safety, and bilirubin kinetics of light-emitting diode (LED) phototherapy to conventional phototherapy in full-term neonates with non-hemolytic hyperbilirubinemia. Methods: From 28th November -26th May 2024, 200 term neonates (≥37 weeks' gestation; birth weight ≥2.5 kg) with total serum bilirubin levels between 15 and 20 mg/dL participated in a single-center randomized controlled trial at DHQ Teaching Hospital, Gujranwala. Participants were randomly assigned to receive either narrow-band LED phototherapy (peak 460 nm; irradiance 35 µW/cm²/nm) or standard fluorescent phototherapy (broad-spectrum; irradiance 15 µW/cm²/nm). Total serum bilirubin was measured at baseline and every six hours until therapy was discontinued. The primary outcome was the rate of bilirubin decline (mg/dL per hour). Secondary outcomes included total phototherapy duration (hours), incidence of hypothermia and hyperthermia, oxidative stress index change, and the need for an exchange transfusion. Results: LED phototherapy had a significantly higher mean bilirubin decline rate (0.19 ± 0.05 mg/dL/hour) than conventional therapy (0.14 ± 0.04 mg/dL/hour). The LED group had a shorter treatment duration (24.3 ± 5.2 hours compared to 29.8 ± 6.1 hours). The LED group had fewer hypothermia and hyperthermia episodes, and their oxidative stress index increased less. No infants in either group needed an exchange transfusion. Conclusion: LED phototherapy is more effective and safer than conventional phototherapy for term neonates with moderate non-hemolytic jaundice. It reduces bilirubin faster, takes less time to treat, and has fewer thermal and oxidative side effects.